VENUS AND MARS: THE TRIUMPH OF THE RENAISSANCE VIRTUE - Flavio Botton (Travessias, 2010)
This paper aims at studyng the characters Venus and Mars, in the works of Botticelli, according to the concepts of Renaissance philosophy Pico della Mirandola and the neoplatonism of Marsilio Ficino.